2016
DOI: 10.4236/ojpsych.2016.62021
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Improves Neurocognition and Treatment Outcomes in Schizophrenia: A Hypothesis

Abstract: There has been a revolutionary advance in the treatment and management of schizophrenia from a clinical aspect yet the social and functional outcomes remain poor. Cognitive function is impaired in schizophrenia and shows various domains of dysfunction like verbal memory, processing speed and working memory. It is also known to be a factor associated with poor outcome in schizophrenia. Resilience is a new concept psychobiological concept which is defined as individual's ability to adapt swiftly to adverse life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 142 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…More recently, it has been hypothesized that cognitive function may influence the course of serious mental illness through its impact on resilience which, in turn, may mediate functional outcomes ( 10 ). The aim of the present study was to compare resilience and cognitive function in patients diagnosed with schizophrenia, patients diagnosed with bipolar disorder, and a sample of healthy controls and to determine if observed deficits in resilience are attributable to deficits in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been hypothesized that cognitive function may influence the course of serious mental illness through its impact on resilience which, in turn, may mediate functional outcomes ( 10 ). The aim of the present study was to compare resilience and cognitive function in patients diagnosed with schizophrenia, patients diagnosed with bipolar disorder, and a sample of healthy controls and to determine if observed deficits in resilience are attributable to deficits in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to clinical remission, secondary resilience may lead to personal growth and developing a meaningful life after mental illness. On the opposite side, lack of resilience determines onset, course, outcome, distress and burden of mental illness (see Shrivastava et al 2016). Tertiary resilience enables patients to develop a healthy and productive way to live with their illness, helps them to adapt to limitations in life associated with illness and have positive and creative life attitudes.…”
Section: Resilence and Treatment Outcome/recoverymentioning
confidence: 99%
“…They reported that these individuals possess resilience through the belief that adversity can be overcome by adhering to cultural values (e.g., religion, family unity, morals, and daily perseverance). Research by Shrivastava, De Sousa, Sonavane, and Shah (2016) led to hypothesising and verifying that an individual's resilience may be linked between positive cognition and the outcome of mental wellbeing.…”
Section: Introductionmentioning
confidence: 99%